2009
DOI: 10.1002/jez.551
|View full text |Cite
|
Sign up to set email alerts
|

Leptodactylus ocellatus (Amphibia): mechanism of defense in the skin and molecular phylogenetic relationships

Abstract: Amphibian antimicrobial peptides have been known for many decades and several of them have already been isolated. However, the number of species investigated is still small. Herein, we report on the skin secretions of Leptodactylus ocellatus, which were extracted by mild electrical stimulation and its semi-preparative reverse-phase chromatography was resolved in more than 30 fractions. Among these fractions, two novel antimicrobial peptides were isolated and their amino acid sequences determined by de novo seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Another hypothesis for the low antimicrobial activity observed is that, in vivo, ocellatins could act synergistically with the various peptides typically present in the skin or with other secreted molecules, as previously described for other peptides. 23,42 However, in our tests, these molecules being absent from our purified samples would not be able to modulate the peptide's activity. Further work is needed to evaluate this hypothesis.…”
Section: Journal Of Natural Productsmentioning
confidence: 96%
“…Another hypothesis for the low antimicrobial activity observed is that, in vivo, ocellatins could act synergistically with the various peptides typically present in the skin or with other secreted molecules, as previously described for other peptides. 23,42 However, in our tests, these molecules being absent from our purified samples would not be able to modulate the peptide's activity. Further work is needed to evaluate this hypothesis.…”
Section: Journal Of Natural Productsmentioning
confidence: 96%
“…In this family, fish produce sound by contracting a sonic muscle against an inflated swim bladder (reviewed in Fine & Parmentier, 2015). In most Sciaenids, males are the prominent sound producers; however, in the Atlantic croaker and black drum, both male and female have sonic muscles and call (Hill, Michael & Musick, 1987; Tellechea et al, 2010). In most cases, sound production is associated with defending territory and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…fallax, Krintler, 1986), and the dermal glands of several species are known to produce defensive skin secretions (Cei et al, 1967), including antimicrobial peptides and other protein toxins found in L. fallax (Rollins-Smith et al, 2005;King et al, 2005a), L. labyrinthicus (Libério et al, 2014), L. laticeps (Conlon et al, 2009), L. latrans (Nascimento et al, 2004(Nascimento et al, , 2007Leite et al, 2010), L. pentadactylus (Habermehl, 1981;Barlow, 1998;King et al, 2005b;Limaverde et al, 2009;Sousa et al, 2009), L. syphax (Dourado et al, 2007). Similarly, the foam nests of L. vastus possess a novel surfactant protein (Hissa et al, 2008(Hissa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%